Training of social workers in Ukraine: problems and their solutions - Андрющенко, А. І.; Горбунова-Рубан, С. О. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2019)
The article analyzes the problems of training social workers to institutions, organizations, services, social orientation. The essence and content of professional work, it emphasizes integrative interdisciplinary.